Inovasi Media Pembelajaran di Era Digital: Menciptakan Lingkungan Belajar yang Interaktif dan Bermakna - Syafruddin Syafruddin; Andi Haris; Indah Dwi Lestari; Nining Andriani; Ade Safitri (Indonesian Journal of Education and Community Services, 2026)
Digital transformation in education requires teachers to be competent in developing innovative, interactive, and meaningful learning media. This Community Service (PkM) activity aims to improve teachers' knowledge and skills in utilizing digital technology as a learning medium. This activity involved elementary school (SD) and junior high school (SMP) teachers in Sumbawa Regency. The implementation method used a participatory approach, encompassing preparation, material delivery, demonstrations, hands-on practice, discussions, mentoring, and evaluation. Training materials covered the use of Canva for Education, Quizizz, Wordwall, Google Forms, and Artificial Intelligence (AI) to support the development of digital learning media. Results showed that participants enthusiastically participated in the entire training series and actively participated in discussions and practice. Teachers were able to understand digital learning concepts and produce more interactive learning media designs tailored to the subjects they taught. In addition to improving technical competency, this activity also encouraged collaboration among teachers in sharing experiences and best practices in implementing technology in learning. Thus, this community service activity positively contributed to improving digital literacy and teacher professional competence, which is expected to support the creation of a more innovative, interactive, and meaningful learning environment and improve the quality of learning in schools.